2016
DOI: 10.1111/irv.12414
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical characteristics of respiratory syncytial virus infections among children and adults in Mexico

Abstract: BackgroundRespiratory syncytial virus (RSV) is a leading etiological agent of acute respiratory tract infections and hospitalizations in children. However, little information is available regarding RSV infections in Latin American countries, particularly among adult patients.ObjectiveTo describe the epidemiology of RSV infection and to analyze the factors associated with severe infections in children and adults in Mexico.MethodsPatients ≥1 month old, who presented with an influenza‐like illness (ILI) to six ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 25 publications
(29 reference statements)
10
22
0
1
Order By: Relevance
“…RSV was the most predominant respiratory virus detected in the patient's samples (35.4% of the patients), while HRV was the second prevalent virus (18.5% of the patients). Our observation is in agreement with others who showed that RSV is the most prevalent virus in patients with respiratory tract infections . In addition to single viral infections, our result demonstrated that mixed viral infections are a frequent phenomenon; it was observed in seven samples indicating that more than one virus can trigger respiratory tract infections and that may influence the severity and outcomes of the respiratory disease.…”
Section: Discussionsupporting
confidence: 93%
“…RSV was the most predominant respiratory virus detected in the patient's samples (35.4% of the patients), while HRV was the second prevalent virus (18.5% of the patients). Our observation is in agreement with others who showed that RSV is the most prevalent virus in patients with respiratory tract infections . In addition to single viral infections, our result demonstrated that mixed viral infections are a frequent phenomenon; it was observed in seven samples indicating that more than one virus can trigger respiratory tract infections and that may influence the severity and outcomes of the respiratory disease.…”
Section: Discussionsupporting
confidence: 93%
“…Even with a cutoff of >40% genome coverage, we identi ed RSV in 79% (although most RSV infections in children are thought to be symptomatic) and CoVs in 47% of HC samples ( Supplementary Table S1). Similarly, this study revealed a high frequency (56%) of RSV-A and RSV-B co-infections in RSV-ARI samples, while previous studies have shown RSV-A and RSV-B coinfections ranging from 0.1% to 0.4% of RSV-ARI 43,44 . The frequency of RSV coinfections was greater in the RSV severe group (69.6%) compared to RSV mild group (37.5%) (Figure 2b).…”
Section: Discussionsupporting
confidence: 71%
“…This analysis is based on data from ILI-002, a hospital-based prospective observational cohort study of ILI [17][18][19]. The present analysis includes all participants enrolled in the ILI-002 study in whom 1 or 2 viruses were detected.…”
Section: Study Populationmentioning
confidence: 99%